In vitro Seed Germination Studies of Drypetes roxburghii (Wall) Hurusava - Sri Rama Murthy, K.; Chandrasekhara Reddy, M. (Indian Forester, 2016)
This study was designed to analyse seed germination barriers and effect of storage duration on the seed viability of Drypetes roxburghii. Present study showed that the hard seed coat was affecting the in vivo seed germination. The decoated seeds showed 83.3% of germination under in vitro conditions on optimum medium of MS + 0.5 mg/l GA3 + 0.01% AC. The seeds of D. roxburghii showed maximum seed viability at storage period of 7 days and declines with further increase of the storage period.